Diffusion measurements in fluids by dynamic light scattering - Fröba, Andreas P.; Leipertz, Alfred (Diffusion Fundamentals, 2005)
In the course of the last thirty years, light scattering techniques have been used with increasing effort and attention for the measurement of the thermophysical properties of pure fluids and fluid mixtures. Here, an introduction is given to dynamic light scattering (DLS) as a valuable tool for the measurement of diffusion processes. First, the basic principles of the method and its experimental realization are presented in some detail. A survey on various applications is given, which especially are related to the determination of transport and other thermophysical properties of transparent fluids. Selected measurements and results are shown for the determination of the thermal diffusivity a in pure fluids and fluid mixtures. For the latter the experimental conditions can turn out to be more complex. The measurement of the mutual diffusion coefficient D12 in binary fluid mixtures, however, is also treated with the simultaneous determination of a which can be realized under certain conditions. In this context beside results for fluids of technical interest, e.g., alternative refrigerants, typical measurements within the critical region for a binary fluid mixture along the critical isochor and a critical separation system are highlighted. Beside a and D12 the application of light scattering from bulk fluids on a molecular level gives also information about sound speed cS, sound attenuation DS, and Landau-Placzek ratio S. For these properties some results from DLS are renewed for the hydrofluorocarbons 1,1,1,2-tetrafluoroethane and pentafluoroethane. Additionally, the measurement of the dynamic viscosity η based on the determination of the diffusion coefficient DP of suspended seed particles is demonstrated for selected pure fluids. The application of DLS to a liquid-vapor interface, also called surface light scattering (SLS), for the simultaneous determination of liquid kinematic viscosity ν and surface tension σ is demonstrated for the important and, thus, well-documented reference fluid toluene, pure refrigerants and their mixtures, and a high viscosity fluid. These measurements demonstrate an excellent performance of the SLS-technique regarding both the achievable high accuracy and the application over a wide range of viscosity.